Paciente femenino de 44 años de edad con anemia hemolítica - Burgos Ruela, Ana Isabel (2018)
The syndrome of hemolytic anemia is a group of pathologies that encompasses a series of signs and symptoms that have as a common manifestation the hemolysis of the red blood cell, which consists of the destruction and / or removal of the red blood cells from the circulation before it is fulfill your average life, that is, 120 days. This entity is of great importance because of its broad spectrum of presentation, which ranges from an asymptomatic picture, an insidious and larvae manifestation, or it can manifest itself as a sudden fulminating picture. In this article we review the main aspects in general of this disease and we propose an algorithm for its diagnostic approach